EFEKTIVITAS FLIPPED CLASSROOM DIINTEGRASIKAN DENGAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN NUMERASI DITINJAU DARI DISPOSISI MATEMATIS SISWA SMA - Siti Lilis Saniah; Hepsi Nindiasari (IKIP Siliwangi, 2023)
The purpose of this study is to find out whether the flipped classroom which is integrated with the discovery learning is better than just using the discovery learning and to find out differences in numeracy abilities when viewed from a mathematical disposition in class XI MAN 4 Tangerang students in the 2021/2022 academic year. This study uses a mix method , namely the combination of quantitative and qualitative. Quantitative research using quasi-experiment design type pretest-post test control group design by making two groups, namely the control class and the experimental class. Methods of data collection using numeracy ability test questions, mathematical disposition questionnaires, observation sheets, and interviews. Data analysis techniques in the quantitative method include normality tests, homogeneity tests, and two-way ANOVA tests (Two-way ANOVA). In the qualitative method, the data analysis used includes data reduction, data presentation, and drawing conclusions. In an effort to improve numeracy skills, the use of the discovery learning integrated with the flipped classroom have a positive impact.